From bean to market: exploring the chemical and production dynamics of high-quality Indonesian vanilla - Munarso, S. Joni; Rahardjo, Yogi P.; Sjafrina, Noveria; Arianto, Arief; Hadipoentyanti, Endang; Astuti, Puji; Setiadi, Adi; Koeslulat, Ermi E.; Lintang, Meivie M. J.; Sulistyorini, Sulistyorini; Egayanti, Yusra; Elmatsani, Huda M.; et al. (Frontiers in Sustainable Food Systems, 2024)
This research investigates the quality of Indonesian vanilla through in-depth interviews with vanilla growers and exporters, as well as quality analysis in the laboratory. Purposive sampling targeted key producers across seven provinces from May to August 2023. Vanilla samples were collected for chemical analysis after a direct interview with each producer. The objective of this research is to identify the chemical composition, production constraints, and post-harvest practices impacting vanilla quality. This knowledge provides input for the ongoing development of international vanilla standards and policy recommendations for the Indonesian vanilla industry. The result show that the physical and chemical qualities of vanilla products fulfil Indonesian standards (SNI). The vanillin content ranged from 1.21 to 3.50. Establishing universal standards requires considering various vanilla varieties and determining minimum quality attribute values. Due to the risk of theft, vanilla pods are often picked when they are less than nine months old, before the fruit is fully ripe. This practice results in a drop in quality, particularly in vanillin concentration. Sustainable growth, stakeholder involvement, inclusive business models, education, and contract farming arrangements help navigate challenges like theft and premature harvesting. Advancements in processing methodologies and the selection of clonal materials reinforce the industry's commitment to enhancing quality